MENINGKATKAN KETERAMPILAN MENYIMAK PERCAKAPAN MENGGUNAKAN MEDIA WAYANG PADA MATA PELAJARAN BAHASA INDONESIA PADA SISWA KELAS III SD AL-RUZHAN - Samrotul, Dede Gina; Deni Chandra; Febri Fajar Pratama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Listening skills are an important part of learning Indonesian. However, third-grade students at Al-Ruzhan Elementary School still experience difficulties in listening to conversations, such as lack of focus, difficulty capturing important information, and not understanding implied meanings. One of the causes is the learning media that is less interesting. This study aims to improve the conversational listening skills of third-grade students at Al-Ruzhan Elementary School through the use of wayang media. This Classroom Action Research (CAR) was carried out in two cycles, each consisting of planning, implementation, observation, and reflection. The results showed a significant increase in students' listening skills. In the first cycle, 12 out of 30 students (40%) achieved scores above the Minimum Completion Criteria (KKM), which is 70. In the second cycle, the number of students who achieved completion increased to 25 students (83.33%). Thus, the use of wayang media has been proven to improve students' listening skills. This media is able to attract attention, increase motivation, and help students focus more in understanding the content of spoken conversations.